"[T]he "[T]he land yields nothing of its speech to us" : Re-Imagining the Nation: Book Review of Wong Phui Nam's An Acre of Day's Glass - Jeyam, Leonard (SARE: Southeast Asian Review of English, 2017)
Book Review